2020
DOI: 10.5334/cstp.283
|View full text |Cite
|
Sign up to set email alerts
|

The Citizens in Citizen Science: Demographic, Socioeconomic, and Health Characteristics of Biodiversity Recorders in Ireland

Abstract: Introduction Citizen science allows members of the public to engage with scientific inquiry, and is increasingly being employed to address environmental change and conservation issues (Turrini et al. 2018; Johnson et al. 2014). There have been many studies focused on the contribution of environmental citizen science to science and research (Ballard, Dixon, and Harris 2017; Chandler et al. 2017; Theobald et al. 2015; Pandya 2012; Raddick et al. 2009). One benefit for researchers is that some projects that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
6
32
0
Order By: Relevance
“…Our study also offers new insights about participation amongst different age groups. We found 25-to 34-yearolds were less likely to have participated in citizen science than people in other age groups, in line with previous studies that have shown higher participation in middleaged and older people (Crall et al 2013;Wright et al 2015;Domroese and Johnson 2017;Mac Domhnaill, Lyons, and Nolan 2020). Again, time constraints may explain the lower rates of participation we observed in this group as they are more likely to have young families and be investing time in building their careers (Merenlender et al 2016).…”
Section: Patterns In Participationsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study also offers new insights about participation amongst different age groups. We found 25-to 34-yearolds were less likely to have participated in citizen science than people in other age groups, in line with previous studies that have shown higher participation in middleaged and older people (Crall et al 2013;Wright et al 2015;Domroese and Johnson 2017;Mac Domhnaill, Lyons, and Nolan 2020). Again, time constraints may explain the lower rates of participation we observed in this group as they are more likely to have young families and be investing time in building their careers (Merenlender et al 2016).…”
Section: Patterns In Participationsupporting
confidence: 90%
“…We have also shown that participation amongst women from minority ethnic groups is particularly low (2.6% of respondents had participated in citizen science compared with 7.4% of women from white ethnic groups and 5.7% of men from minority ethnic groups, and less than 1% of this group had participated more than once). Unemployed people and those from lower socio-economic groups were also shown to be underrepresented, with 3.3% of the lowest socio-economic group compared with 15.9% of the highest having participated, confirming for Great Britain patterns observed in other countries (Trumbull et al 2000;Overdevest, Orr, and Stepenuck 2004;Evans et al 2005;Crall et al 2013;Mac Domhnaill, Lyons, and Nolan 2020). These patterns reflect barriers to participation in citizen science identified previously, which are likely to have a particular impact on marginalised groups.…”
Section: Patterns In Participationsupporting
confidence: 71%
See 1 more Smart Citation
“…Citizen science participation is currently unevenly distributed between different sectors of society, limiting the social value citizen science has the potential to deliver (Brouwer and Hessels 2019) and perhaps also having implications for the data that are generated . Analyses of the demographics of participants in environmental citizen science projects that come primarily from Europe and North America show that participants are predominantly from white ethnic groups (Wright et al 2015;Merenlender et al 2016;Domroese and Johnson 2017), and are highly educated (Evans et al 2005;Trumbull et al 2000;Mac Domhnaill et al 2020), affluent (Hobbs and White 2012;Overdevest et al 2004), and middle aged or older (Domroese and Johnson 2017;Crall et al 2013), a pattern that holds across citizen science more broadly (NASEM 2018).…”
Section: Addressing Unevenness In Participation Through Tailored Appr...mentioning
confidence: 99%
“…Apart from these scientific benefits, there is growing evidence that time in the outdoors, and volunteering specifically, are beneficial to participants themselves (e.g. Mac Domhnaill et al, 2020; Peter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%